38OTalazoparib (TALA) vs physician's choice of chemotherapy (PCT) in Asian patients (Pts) with HER2- advanced breast cancer (ABC) and a germline BRCA1/2 mutation (gBRCA1/2mut): Data from phase III EMBRACA. (24th November 2019) - Lee, K-H; Kim, S-B; Sohn, J; Goodwin, A; Usari, T; Lanzalone, S; Im, Y-H
Abstract: Background: The oral PARP inhibitor TALA is approved in multiple countries (US/EU/ARG/UAE) for HER2- gBRCA1/2mut ABC. To date, limited information is available on use of TALA in Asian pts. Methods: EMBRACA (NCT01945775) is an ongoing randomized study comparing TALA 1 mg/day vs PCT in HER2- gBRCA1/2mut ABC. Primary endpoint: progression-free survival (PFS) by blinded review; secondary endpoints: PFS by investigator; objective response rate (ORR); safety (adverse events [AEs]). Endpoints were assessed in Asian pts (APAC; Korea, Taiwan) and in the intent-to-treat (ITT) population. Results: 431 pts were randomized (TALA: ITT 287, APAC 23; PCT: ITT 144, APAC 10). In APAC pts, median age was 41.0 and 45.0 y in TALA and PCT, with 73.9% and 60.0% aged <50 y, respectively; ITT median age was 45.0 and 50.0 y, with 63.4% and 46.5% aged <50 y, respectively. In APAC pts, triple-negative (42.4%) and hormone-receptor–positive (57.6%) disease were consistent with ITT pts. TALA was more effective than PCT in APAC pts, similar to ITT pts (Table). In APAC pts receiving TALA, most common (≥10%) hematologic AEs were neutropenia (34.8%), anemia (17.4%), platelet count decrease (13.0%), thrombocytopenia (13.0%), and neutrophil count decrease (8.7%); common (≥30%) non-hematologic AEs were nausea (47.8%), fatigue (43.5%), URTI (30.4%), and decreased appetite (30.4%). AEs were generally consistent with ITT. Median relative dose intensity (actual-dose intensity/planned-dose intensity) for TALA was 99.7% APAC and 87.2% ITT. No APAC pts permanently discontinued due to AEs in either arm; 5.9% (TALA) and 8.7% (PCT) permanently discontinued due to AEs in ITT. Conclusions: In pts with HER2- gBRCA1/2mut ABC, TALA improved outcomes vs PCT. Results in a limited number of enrolled Asian pts were generally consistent with the ITT population. Clinical trial identification: NCT01945775. Editorial acknowledgement: Editorial support, under the direction of the authors, was provided by Ann Gordon, PhD, of CMC AFFINITY, a division of McCann Health Medical Communications Ltd., Glasgow, UK, funded by Pfizer Inc. Legal entity responsible for the study: Pfizer. Funding: Pfizer (Medivation). Disclosure: K-H. Lee: Honoraria (institution), Advisory / Consultancy: Roche; Honoraria (institution), Advisory / Consultancy: AstraZenceca; Advisory / Consultancy: Bayer; Advisory / Consultancy: Ono pharmaceutical; Advisory / Consultancy: Samsung bioepis; Advisory / Consultancy: Eisai. S-B. Kim: Research grant / Funding (institution): Novartis. J. Sohn: Research grant / Funding (institution): MSD; Research grant / Funding (institution): Roche; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Lilly; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): GSK; Research grant / Funding (institution): CONTESSA; Research grant / Funding (institution): Daiichi Sankyo. A. Goodwin: Travel / Accommodation / Expenses: Pfizer; Travel / Accommodation / Expenses: AstraZeneca; Travel / Accommodation / Expenses: Roche; Travel / Accommodation / Expenses: Novartis; Travel / Accommodation / Expenses: Amgen; Travel / Accommodation / Expenses: Celgene; Travel / Accommodation / Expenses: Boehringher. T. Usari: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer Inc. S. Lanzalone: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer Inc. All other authors have declared no conflicts of interest.